Pengembangan Modul Basic Training (Latihan Kader I) Berbasis Digital pada Perkaderan Himpunan Mahasiswa Islam (HMI) Cabang Langkat - Putra, Alwanda; Mardianto, Mardianto; Salminawati, Salminawati (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study aims to develop and test the feasibility and effectiveness of a digital-based Basic Training module (Latihan Kader I) to support the regeneration process of the Langkat Branch of HMI. The method used is research and development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were obtained through observation, interviews, questionnaires, pre- and post-tests, and documentation, then analysed descriptively using paired t-statistical tests. The validation results showed that the module met the "outstanding" category, with scores of 92.5% (subject matter experts), 90% (design experts), 93.3%–94.2% (instructors), and 90.5%–95.6% (participants). Effectiveness testing on 20 participants showed a significant increase in the average score from 61.75 (pre-test) to 87.75 (post-test), t(19) = 17.09, p < 0.000001, with Cohen's d = 3.82 (huge effect). The module's effectiveness was supported by applying the principles of the Cognitive Theory of Multimedia Learning, which integrates text, visuals, and interactive exercises to reduce cognitive load and enhance retention. Despite the positive findings, limitations of the study include the absence of a control group, small sample size, potential novelty effect, and limited generalizability. This module has the potential for broader adoption with replication in different contexts, implementing follow-up tests, and measuring skills and attitudes. Further research is recommended to identify the most influential components of the module, assess user acceptance through TAM or UTAUT, and evaluate the impact on organisational performance.